Botanic Gardens, Port of Spain, Trinidad, B.W.I. - (:unkn) unknown (James Book Store, 2010)
The postcard shows trees including varieties of palm trees in the Botanical Gardens in Trindad.
Colour: Hues of orange and green; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Botanical gardens--Trinidad and Tobago; Palms--Trinidad and Tobago; Plants--Trinidad and Tobago